2014
DOI: 10.1080/10298436.2014.937713
|View full text |Cite
|
Sign up to set email alerts
|

Binder distribution model for asphalt mixtures based on packing of the primary structure

Abstract: Film thickness describes the coating around aggregate particles on asphalt mixtures. The standard method of calculating film thickness has proven to present several limitations, such as assuming an average thickness independent of particle size, being completely independent to the porosity of the mixture and considering only one mineral type. In this paper, a binder distribution model is developed for aggregates according to size and role in the structure. The aggregates are separated into two different struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…The gradation-based framework developed in this study defines a primary and a secondary aggregate structure, respectively, and identifies these structures in asphalt mixtures given the particle size distribution. Furthermore, the gradation-based framework was used by Das, Birgisson, Jelagin, and Kringos (2013) to investigate the relationship between coating thickness of the primary structure (Lira, Jelagin, & Birgisson, 2015) and the ageing characteristics of an asphalt mixture. The authors observed a direct correlation between primary structure coating thickness and age hardening of asphalt mixtures.…”
Section: Introductionmentioning
confidence: 99%
“…The gradation-based framework developed in this study defines a primary and a secondary aggregate structure, respectively, and identifies these structures in asphalt mixtures given the particle size distribution. Furthermore, the gradation-based framework was used by Das, Birgisson, Jelagin, and Kringos (2013) to investigate the relationship between coating thickness of the primary structure (Lira, Jelagin, & Birgisson, 2015) and the ageing characteristics of an asphalt mixture. The authors observed a direct correlation between primary structure coating thickness and age hardening of asphalt mixtures.…”
Section: Introductionmentioning
confidence: 99%
“…As stated above this assumption is made here for simplicity and more realistic binder phase distribution models, such as e.g. (Lira, Jelagin, & Birgisson, 2015) will be incorporated as a part of future studies. 4π 3…”
Section: Geometrymentioning
confidence: 99%